La musicologia afro-americana e il documento sonoro. Aspetti fondativi e disciplinari - Cerchiari, Luca (Musica/Tecnologia, 2009)
Afro-American musicology and the sound document. Disciplinary and foundation aspects After an introduction about the production of sound documents, both written and recorded, within Afro-American music, the author considers the importance of the subject of jazz documentation in terms of sound and the basic contribution to discography within these repertoires. The contribution given by the sound document to Afro-American musicology and its didactics, in addition to the transmission of contents, has a primary importance: transcriptions of solos and improvisations, analyses and comparisons, these are the basis of studies done directly on sound documents. Mentioned are also other types of documents, such as pianola rolls and mechanical instruments. The contribution to ancillary information connected to sound documents is considered (record envelopes, containers, illustrated booklets, cover notes) as well as the importance of the whole production process to the creation of collections and sound archives, both public and private ones, based on that repertoire, giving birth also to restoration and retrieval activities.